"O negro toca, o negro canta e o negro dança, foi lá no meu terreiro que aprendi desde a infância": a prática cultural do samba enquanto uma encruzilhada de experiências e agências afro-diaspóricas - Grosso, Laura Mendes (Universidade Federal de São Carlos, 2024)
This research was interested in the cultural practice of samba, especially in the city of Londrina (PR). The main sociological problem that guided the work is around the following question: to what extent does the cultural practice of samba politically position the experience and agency of the Afro-diasporic subject? In view of this, the work aimed to analyze the extent to which the cultural practice of samba is constituted as part of black agency in Londrina (PR). In order to get closer to this interest, three specific objectives were set: a) to identify the social issues surrounding the black population in the city; b) to outline the meanings of this cultural practice for black samba dancers in Londrina; c) to analyze whether and how the black agency constituted in the city through the practice of samba, tensions the narratives produced around the cultural differences of the municipality and helps to construct and narrate the paths and history of the black population in the city. To this end, the research is anchored in a central argument: that Afro-diasporic subjects have inscribed themselves in Brazil through an individual and collective agency based on three principles: crossroads, Exu and enchantment. We argue that it is operated through a “mandingueiro doing”, which finds its place par excellence in samba. Samba is more than just a musical genre, it is a cultural practice based on a continuum of playing-dancing-singing and enchantment, which feeds back into the body and the black experience in the African diaspora. The research, articulated with post-colonial theories and cultural studies, was built through documentary research in the Folha de Londrina newspaper (NDPH-UEL) and semi-structured interviews. In addition to tracing the potential of the philosophies and way of life of samba from London's samba dancers, we found a 58-year history of samba schools in the municipality that informed another type of sociability.
The black man plays, the black man sings and the black man dances, it was there in my terreiro that I learned from childhood: the cultural practice of samba as a crossroads of afro-diasporic experiences and agencies
Keywords: Diáspora africana; Agência negra; Prática cultural do samba; Corpo-memória; Encruzilhadas; African diaspora; Black agency; Cultural practice of samba; Body-memory; Crossroads; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS